2023
DOI: 10.1002/ccd.30600
|View full text |Cite
|
Sign up to set email alerts
|

Complex primary percutaneous coronary intervention with ultrathin‐strut biodegradable versus thin‐strut durable polymer drug‐eluting stents in patients with ST‐segment elevation myocardial infarction: A subgroup analysis from the BIOSTEMI randomized trial

Abstract: Background: Ultrathin-strut biodegradable polymer sirolimus-eluting stents (BP-SES) are superior to thin-strut durable polymer everolimus-eluting stents (DP-EES) with respect to target lesion failure (TLF) at 2 years among patients with ST-segment elevation myocardial infarction (STEMI). We sought to determine the impact of primary percutaneous coronary intervention (pPCI) complexity on long-term clinical outcomes with BP-SES versus DP-EES in STEMI patients.Methods: We performed a post hoc subgroup analysis fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A post hoc subgroup comparison study from the BIOSTEMI randomized trial showed that ultrathin-strut biodegradable polymer sirolimus-eluting stents performed better than thin-strut durable polymer everolimus-eluting stents regarding the target lesion failure at two years among STEMI patients having undergone both complex and noncomplex primary percutaneous coronary intervention [58].…”
Section: Patient-specific Stentsmentioning
confidence: 99%
“…A post hoc subgroup comparison study from the BIOSTEMI randomized trial showed that ultrathin-strut biodegradable polymer sirolimus-eluting stents performed better than thin-strut durable polymer everolimus-eluting stents regarding the target lesion failure at two years among STEMI patients having undergone both complex and noncomplex primary percutaneous coronary intervention [58].…”
Section: Patient-specific Stentsmentioning
confidence: 99%